THE ANALYSIS OF READING MATERIALS IN SENIOR HIGH SCHOOL TEXTBOOK GRADE X BASED ON KTSP - Firdaus, Muhammad Farhan; Al Fatih, Muhammad; Ismariyanto, Arda Mageso; Ikaningrum, Rini Estiyowati (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2024)
The purpose of this study was to describe whether the reading material in English textbooks for 10th-grade high school students was by KTSP, and the school fulfilled the content, language use, and readability aspects, as well as the advantages and disadvantages of the 10th-grade reading material through swot analysis. The researcher uses the descriptive qualitative method for a detailed explanation. The results will be described in words without any statistical calculations. The data were collected from the reading section of the textbook and, more importantly, the SWOT analysis results as a complement to the explanation of the previous explanation. The checklist form was used during the research analysis. The findings show that the strength and weaknesses of each material and learning will be found.